ANALISIS INTERAKSI EDUKATIF ANTARA GURU DAN PESERTA DIDIK KELAS XII SMAN 1 JAWAI - Rismunandar, Reza; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine the interaction between teachers and students in economic learning. The method in this research uses descriptive qualitative method with the form of research, namely case study research. The subjects of this study were 30 teachers of class XII SMA Negeri 1 Jawai. The data collection techniques used in this research are direct observation techniques with data collection tools in the form of observation sheets of student learning activities, interviews, and documentation. The indicators seen from economic learning activities (1) attract students' attention (2) motivate students (3) structure of the lesson (4) remind the topics that are mastered with new topics (5) respond to situations (6) convey information (7) explain giving motivation (8) Express personal opinion (9) Focus attention (10) Summarize the main points of the lesson (11) Provide psychological encouragement to students (12) Provide instructions for subsequent lessons (13) Conduct evaluation. Based on the data, the results can be obtained and it can be concluded that the educational interaction between teachers and students is quite good.Keywords: Economic, Educational Interactionslphabetic, Learning